Tendencies of mortality by prostate cancer in the states of the Central-West Region of Brazil, 1980 - 2011 - João Francisco Santos da Silva; Inês Echenique Mattos; Ricardo Dutra Aydos (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
This study aimed at analyzing the pattern of prostate cancer mortality in the Central-West Region, in the period 1980 - 2011. The quadrennial and annual mortality rates, age-standardized by the world population, were calculated. Polynomial regression models were estimated to analyze trends of mortality in Brazilian regions and in the states of the Central-West Region. Throughout Brazil there was an increase in the magnitude of mortality rates during the study's period. In the Central-West Region, mortality rates from prostate cancer increased from 7.65/100,000 in the period 1980 - 1983, to 14.36/100,000 in the last four years, exceeding the national average. For Mato Grosso do Sul, an increased trend, although not constant, was observed for prostate mortality rates, while those rates showed stability for Mato Grosso and presented a constant trend of increment for Goiás along the studied period. There was a statistically significant negative correlation between mortality rates from prostate cancer and the proportional mortality from ill-defined causes of death in the three states, but no correlations were observed between these rates and the ratios of Prostate Specific Antigen (PSA) tests realized. Difficulties in the access to the health services network, better quality of death records with reduction of ill-defined causes and increased use of PSA may have contributed to the mortality pattern observed in the Central-West Region. Further studies are needed to investigate these relationships in order, to better understand the patterns of mortality from this cancer in the Central-West population.